China's building energy efficiency standards assessment based on fuzzy evaluation algorithm. Issue 6 (7th November 2019) - Wang, Jingjing; Zhang, Yurong; Wang, Yuanfeng; Gu, Lin
Abstract : Building energy efficiency (BEE) is regarded as the key sector in the world for addressing climate change and energy problems, since buildings consume around one-third of global energy and produce a substantial amount of greenhouse gas emissions. It is important to utilise BEE standards (BEESs) to ensure that cost-effective energy efficiency opportunities are incorporated into new and existing buildings. A key question is how the actual performance of BEESs can be measured so that they are developed in a more sustainable way. An effective method that can evaluate BEESs from both quantitative and qualitative perspectives is provided, and it fulfils a dual step: ( a ) determining a BEES evaluation indicator system, including technological, economical and social indicators, by identification, correction and selection; and ( b ) establishing the BEES evaluation model: a fuzzy synthetic evaluation model based on the information entropy theory with the analytic hierarchy process. The developed BEES evaluation model and the case study of China's 'Design standard for energy efficiency of public buildings' could provide a comprehensive framework to understand the energy efficiency performance of BEESs in China. The results will help improve the management of BEESs and ensure more sustainable building practice.